Implementasi Etika Bisnis Dan Manajemen Bisnis Islam di Konveksi Duta Collection's Yayasan Darut Taqwa - winda Wijiati; Moh. Mukhsinin Syu’aibi; Ifdlolul Maghfur; M. Dayat (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2023)
This study aims to analyze the practice of Islamic business ethics and business management at the Darut Taqwa Sengonagung konveksi Duta Collection’s Foundation. Darut Taqwa Sengonagung Foundation is a non-profit organization engaged in retail management, especially in the field of uniform collections for students and female students. Against this background, this study examines how Islamic business ethics are applied in the daily operations of Yayasan Darut Taqwa Sengonagung konveksi Duta Collection’s and how Islamic business management principles are used in the process. This study uses a qualitative approach with in-depth interviews and direct observation as a data collection method. The results of the study show that the Darut Taqwa Sengonagung konveksi duta collection’s Foundation applies Islamic business ethical values in its practice. Principles such as honesty, integrity, fairness and social responsibility are the cornerstones of business relationships with customers, suppliers and business partners. In managing the business, the fund uses sharia management principles such as shura (advise), amanah (trust) and ihsan (do good) to make strategic decisions. However, this research also reveals some challenges in implementing Islamic business ethics and business management at the Darut Taqwa Sengonagung Konveksi Duta Collection’s Foundation. Some of these challenges include the difficulty of maintaining a balance between business goals and Islamic values, as well as the limited human resources that understand the concept of business ethics and business management. Muslim business. This study contributes to understanding the practice of Islamic business ethics and business management in the retail sector, particularly in the context of platforms. The results of this study should become a benchmark for similar organizations in applying Islamic business ethics and business management principles to achieve long-term sustainability and profitability.